Carbon footprint analysis and advanced exergo-environmental modeling of a waste heat recovery system based on a recuperative organic Rankine cycle (2020)
The excessive and irrational use of non-renewable energy is the consequence of the interaction of economic growth and environmental pollution. Therefore, it is increasingly necessary to propose energy and environmental improvements in the energy conversion systems according to sustainable development goals, especially in internal combustion engines. The exergetic analyses are a great tool because they allow identifying the components of greater irreversibilities. However, sustainable continuous improvement and opportunities can be found only by means of its advanced development. The study showed that in the waste heat recovery of a 2 MW gas engine based on the recuperative organic Rankine cycle (RORC) using R123 as working fluid, much of the exergy destroyed was endogenous 105.08 kW (81.6%). Steel, copper and aluminum were the proposed materials for the construction of the components, and through a life cycle analysis, it was found that the significant environmental impacts were found in the turbine for the aluminum with a value of 27617.21 kg of CO2 equivalent. Through the carbon footprint and advanced exergo-environmental analysis, it was found that the heat exchanger 1 is the equipment with the largest endogenous exergy destruction opportunities for improvement, also is the heat exchanger device with the most significant rate of environmental impacts, and the recommended material to use in the construction phase of the life-time of the system is the aluminum.